THE IMPACT OF ARTIFICIAL INTELLIGENCE IN THE CONCLUSION OF THE PLEA AGREEMENT - Paraschiv, Carmen Silvia (International Journal of Legal and Social Order, 2026)
The digital transformation of the judicial system has made artificial intelligence (AI) an increasingly important vector in the analysis of evidence, in the formulation of plea agreements, and in the anticipation of judicial outcomes (Susskind, 2019; Surden, 2020). The article investigates the impact of these technologies in the context of plea bargaining, highlighting the tension between procedural efficiency and fundamental guarantees of a fair trial (Angwin et al., 2016; Katz, 2020). AI can reduce the length of cases and standardize practice, but it brings risks related to voluntarism, transparency, equality of arms, and accountability (Goodman & Flaxman, 2017; Floridi, 2021). Predictive models that estimate the probability of conviction or suggest sentences can influence the decision-making autonomy of the defendant (Wachter & Mittelstadt, 2019). The main proposal is to establish a regulatory framework focused on meaningful human control, algorithmic audit and data protection (CEPEJ, 2021), so that the final decision remains a responsible and fair human act. Conclusion: AI can support criminal justice only if it is used transparently, ethically and under constant legal supervision (Dignum, 2022).